2016
DOI: 10.1371/journal.pone.0161462
|View full text |Cite
|
Sign up to set email alerts
|

How Climate Change Beliefs among U.S. Teachers Do and Do Not Translate to Students

Abstract: Research suggests climate change beliefs among science teachers mirror those of the general public, raising questions of whether teachers may be perpetuating polarization of public opinion through their classrooms. We began answering these questions with a survey of middle school science teachers (n = 24) and their students (n = 369) in North Carolina, USA. Similar to previous studies, we found that though nearly all (92.1%) of students had teachers who believe that global warming is happening, few (12%) are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
1
29
0
4
Order By: Relevance
“…According to Herman et al, "there need to be science teachers whose knowledge and perceptions are in line with those of vast majority of scientists" [23]. Investigations of student teachers', pre-service teachers', and teachers' climate change-related knowledge displayed deficits [23][24][25][26][27][28][29]. In their study, Herman et al [23] reported that only 14% of science teachers in Florida and 4% in Puerto Rico gave the correct definition of climate change.…”
Section: Student Teachers' Knowledge Of Sd-related Topicsmentioning
confidence: 99%
“…According to Herman et al, "there need to be science teachers whose knowledge and perceptions are in line with those of vast majority of scientists" [23]. Investigations of student teachers', pre-service teachers', and teachers' climate change-related knowledge displayed deficits [23][24][25][26][27][28][29]. In their study, Herman et al [23] reported that only 14% of science teachers in Florida and 4% in Puerto Rico gave the correct definition of climate change.…”
Section: Student Teachers' Knowledge Of Sd-related Topicsmentioning
confidence: 99%
“…Therefore, along with the contribution of general media, the systematic instruction provided by teachers in schools about climate change is important for the construction of young people's knowledge and beliefs of young people in this field (Dupigny-Girouz, 2010;Ekborg & Areskoug, 2006;Schreiner, Henriksen, Kirkeby, & Pål, 2005). Strong knowledge about climate change is shown to help teachers succeed in this task (McNeal, Petcovic, & Reeves, 2017;Sadler, Amirshokoohi, Kazempour, & Allspaw 2006), and their beliefs about the causes of climate change are known to influence their pupils (Stevenson, Peterson, & Bradshaw, 2016). they motivated to fulfill their role.…”
Section: Climate Change and Teachers' Educationmentioning
confidence: 99%
“…The research questionnaire contained numerous items from two published questionnaires about global warming and several original items (see hereunder). The first questionnaire used was excerpted from the Six Americas' Survey developed by the Yale Project on Climate Change Communication (Leiserowitz, Maibach, Roser-Renouf, & Smith, 2011;Leiserowitz, Smith, & Marlon, 2012) which has been used in several recent research works with teachers (Lambert & Bleicher 2013;Shea et al, 2016;Stevenson et al, 2016;Valdez, Peterson, & Stevenson, 2018) as it reflects better than earlier designed questionnaires the knowledge that has developed recently in the global population about climate change. The second questionnaire was developed by Tobler, Visschers, and Siegrist (2012) in Switzerland and contains more items concerning beliefs.…”
Section: Research Questionnairementioning
confidence: 99%
“…Schools are an obvious channel through which to engage young people in the key issues associated with climate change, although formal education about the issue is not without its challenges. These include the one-way communication models that separate transmitter and receiver; the lack of critical approaches, evidenced by the absence of spaces for reflection and debate on possible alternative lifestyles; and the lack of opportunities to participate in bringing about in-depth learning (Lombardi and Sinatra 2013;Plutzer et al 2016;Stevenson, Peterson, and Bradshaw 2016). Furthermore, climate change is surrounded by 'fake news' promoted by sceptics, a phenomenon that has put teachers on the alert and encouraged them to embrace media literacy: 'the ability to access, understand, evaluate, and create media content' (Cooper 2011).…”
Section: Introductionmentioning
confidence: 99%